Factors Associated with 24-hour Mortality of Patients Rescued by Emergency Aeromedical Team of Somdejprajaotaksin Maharaj Hospital - Phetprasert, Theerarat; Peeracheir, Sivanath (Lampang Medical Journal, 2021)
Background: Emergency aeromedical services have been operational in Tak Province since 2012 to help the critically-illed patients from the remote mountainous areas, and subsequently developed by Somdejprajaotaksin Maharaj Hospital. The outcome of this service has not been investigated. Study Objective: To determine the outcomes of emergency aeromedical service by Somdejprajaotaksin Maharaj Hospital and factors associated with the 24-hour mortality. Materials and methods: A cross-sectional descriptive study was conducted among the emergent patients who were transported with helicopters by the aeromedical service of Somdejprajaotaksin Maharaj Hospital between January 2015 and September 2020. Demographic and transportation data were analyzed and compared between the patients who survived and died within 24 hours after transfer using an exact probability test. Results: There were 40 patients who received 38 flights of aeromedical transport. Most of them were helicopter emergency medical service (70%). Two-thirds of the patients lived in Umphang District. The most common disease groups were critically-illed children (25.0%), obstetrics-gynecology (22.5%) and newborn (10.0%). Fifty-five percent of helicopters were supported by the Thai Army. Four patients died within 24 hours after hospitalization and the mortality rate was 10%. Age, gender, disease group, level of acuity, mission type, destination hospital, flight activation time, total mission time and personnel in aeromedical team were not associated with the 24-hour mortality. Conclusion: The 24-hour mortality rate of emergent patients rescued by emergency aeromedical team of Somdejprajaotaksin Maharaj Hospital was 10%. There were no significant factors associated with this mortality.